2019
DOI: 10.1126/science.aaz3418
|View full text |Cite
|
Sign up to set email alerts
|

DNA loop extrusion by human cohesin

Abstract: Eukaryotic genomes are folded into loops and topologically associating domains, which contribute to chromatin structure, gene regulation, and gene recombination. These structures depend on cohesin, a ring-shaped DNA-entrapping adenosine triphosphatase (ATPase) complex that has been proposed to form loops by extrusion. Such an activity has been observed for condensin, which forms loops in mitosis, but not for cohesin. Using biochemical reconstitution, we found that single human cohesin complexes form DNA loops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
786
8
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 709 publications
(888 citation statements)
references
References 47 publications
49
786
8
5
Order By: Relevance
“…Thus, downmodulation of CTCF-bound scanning-impediment activity promotes cohesin-driven RAG-scanning across the 2.7Mb Igh locus.Cohesin is a highly conserved chromosome-associated multi-subunit ring-shaped ATPase complex built upon subunits belonging to the structural maintenance of chromosomes (Smc) family and is important for diverse chromosome-based processes [28][29][30][31][32][33] .The cohesin complex is proposed to form contact loop domains by extrusion of chromatin until reaching convergent CTCF-bound CBE anchors 2-10 . In this regard, cohesin extrudes both naked and nucleosome-containing DNA in an NIPBL-MAU2 and ATP-hydrolysisdependent manner in vitro 34,35 . Our studies implicated the cohesin complex in chromatin loop extrusion-mediated mechanisms of lymphocyte V(D)J and IgH class switch recombination 11,[14][15][16]36,37 .…”
mentioning
confidence: 99%
“…Thus, downmodulation of CTCF-bound scanning-impediment activity promotes cohesin-driven RAG-scanning across the 2.7Mb Igh locus.Cohesin is a highly conserved chromosome-associated multi-subunit ring-shaped ATPase complex built upon subunits belonging to the structural maintenance of chromosomes (Smc) family and is important for diverse chromosome-based processes [28][29][30][31][32][33] .The cohesin complex is proposed to form contact loop domains by extrusion of chromatin until reaching convergent CTCF-bound CBE anchors 2-10 . In this regard, cohesin extrudes both naked and nucleosome-containing DNA in an NIPBL-MAU2 and ATP-hydrolysisdependent manner in vitro 34,35 . Our studies implicated the cohesin complex in chromatin loop extrusion-mediated mechanisms of lymphocyte V(D)J and IgH class switch recombination 11,[14][15][16]36,37 .…”
mentioning
confidence: 99%
“…During G2, about half of all chromatin-bound cohesin dynamically turns over 44,45 to form cis-chromatid loops that shape TADs 6,16 , whereas the other half binds the stabilizing factor Sororin 27,46 and persistently links sister chromatids. Trans sister contacts might concentrate at TAD boundaries because of motor-driven loop extrusion 20,21 or via a mechanism involving cohesin independently of DNA loops. To investigate these possibilities, we aimed to selectively deplete the pool of cohesin that forms chromatin loops without disrupting sister-chromatid cohesion.…”
Section: Molecular Control Of Sister-chromatid Topologiesmentioning
confidence: 99%
“…To investigate these possibilities, we aimed to selectively deplete the pool of cohesin that forms chromatin loops without disrupting sister-chromatid cohesion. The cohesin loading factor NIPBL is required to extrude and maintain cischromatid loops formed by cohesin 15,20 , but it is not expected to be required to maintain cohesion, given that this is mediated by persistently bound cohesin 44 . To test this hypothesis, we homozygously tagged NIPBL with auxin-inducible degrons (AID) 47 , synchronized cells to G2 and added auxin to induce NIPBL degradation (Extended Data Fig.…”
Section: Molecular Control Of Sister-chromatid Topologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vitro experiments have demonstrated that cohesin and condensin complexes indeed can extrude loops in an ATP-dependent mechanism [44][45][46][47] . These observations provide strong support for the model in which loop extrusion events throughout the cell cycle guide topoisomerase II activity to generate and maintain a largely decatenated genome as we detect here.…”
Section: Mc-3c Data Can Reveal Entanglements At Chromosome and Domainmentioning
confidence: 99%